Developing A Project Management Maturity Model to Enhance Execution Performance in Solar EPCProjects: A Case Study of an Engineering, Procurement, and Construction (EPC) Company - Iftikar Fadhlirohman Soeroyo; Gatot Yudoko (Journal Research of Social Science, Economics, and Management, 2026)
PT TML Energy, an Engineering, Procurement, and Construction (EPC) company specializing in solar energy projects in Indonesia, experienced recurring project execution delays of 20–40% beyond planned schedules during 2021–2024. A review of project records indicated that these delays stem not from technical limitations but from systemic weaknesses in project management maturity. This study assesses the current level of project management maturity and develops a tailored Project Management Maturity Model to improve execution performance. A mixed-methods approach was applied: qualitative semi-structured interviews with four key informants explored why delays occur, while a quantitative questionnaire of twenty respondents measured maturity across seven PMBOK Knowledge Areas using Crawford’s (2014) Project Management Maturity Model. The qualitative analysis produced seven Knowledge-Area themes and identified five interconnected root causes of delay: absence of integrated pre-project planning, reactive and fragmented procurement, experience-dependent scheduling, informal communication, and absence of organizational learning. While the questionnaire placed the company at Level 4 (mean = 3.86), triangulation with interview evidence revealed a self-assessment inflation of approximately 1.3 levels, indicating an operational maturity at the upper boundary of Level 2. Five integrated business solutions were developed: an Integrated Project Management Plan template, a procurement lead-time integration framework, a parametric schedule database, a communication management plan template, and a lessons-learned database with a competency development framework. The findings demonstrate that single-method maturity assessments tend to overstate maturity, and that mixed-methods triangulation produces a more accurate and actionable maturity profile for emerging-market EPC contractors.